A coating for wind turbine blades and a method for its preparation

CN122772431APending Publication Date: 2026-09-18SHENZHEN LIJIAN BONA TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610776168.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-01
Publication Date
2026-09-18

AI Technical Summary

Technical Problem

[0003]市面上常见的风电叶片涂料多以传统的聚氨酯或环氧体系为主,而抗冲蚀要求涂层同时具备高硬度和高韧性;聚氨酯体系涂层,虽能缓冲冲击,但硬度与模量偏低,在尖锐沙粒的持续“微切削”作用下,磨耗率极高;环氧体系涂层,虽耐磨,但脆性高,在高速粒子冲击下,易在冲击点周边产生放射状微裂纹,这些微裂纹在后续应力作用下迅速扩展、互联,导致涂层宏观碎裂和片状剥落

Benefits of technology

1、本申请将纳米增韧填料和分散耐磨填料搭配使用时,通过二者间的协同复配,不仅利用橡胶粒子吸收能量,鳞片分散应力,使冲击能被多级消耗,而非单一传导,还能使裂纹遇到鳞片发生偏转和绕射,遇到橡胶粒子发生钝化和分支,进而在涂层内部形成刚柔并济的微观结构,如此既能抵抗高速粒子的切入和切削,又能高效吸收和分散冲击动能,实现硬度与韧性的最优平衡,进而显著延长风电叶片在高速粒子冲蚀下的使用寿命;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1778479993091-000001
    Figure REF-OBJ-1778479993091-000001
  • Figure REF-OBJ-1778479993091-000002
    Figure REF-OBJ-1778479993091-000002
Patent Text Reader

Abstract

This application relates to the field of coating technology, specifically disclosing a coating for wind turbine blades and its preparation method. A coating for wind turbine blades includes component A and component B, which are stored separately and mixed in a weight ratio of (4-5):1 when used. Component A contains the following raw materials in parts by weight: 40-60 parts hydroxyl acrylic resin, 0.5-2 parts ultraviolet absorber, 0.5-2 parts light stabilizer, 1-1.5 parts dispersant, 0.2-0.6 parts leveling agent, 0.1-0.3 parts defoamer, 10-25 parts solvent, 8-15 parts nano-toughening filler, and 12-20 parts dispersing abrasion-resistant filler. The nano-toughening filler is a core-shell structured rubber particle, with a core of butadiene-butyl acrylate copolymer and a shell of polymethyl methacrylate. The dispersing abrasion-resistant filler is glass flakes or ceramic flakes surface-treated with a silane coupling agent. Component B is a curing agent. The coating structure formed by the coating material for wind turbine blades in this application can resist the cutting and abrasion of high-speed particles, and can also efficiently absorb and disperse impact kinetic energy, resulting in a better service life under the erosion of high-speed particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of coating technology, and more specifically, to a coating for wind turbine blades and a method for preparing the same. Background Technology

[0002] Wind turbine blades are the core components for capturing wind energy, and their aerodynamic shape and surface integrity have a decisive impact on wind energy utilization efficiency, operational stability, and service life. As the wind power industry expands into low-wind-speed, offshore, desert, and high-altitude areas, the operating environment faced by blades is becoming increasingly harsh. Especially under high-speed rotational conditions with tip linear velocities reaching 80-100 m / s (equivalent to 290-360 km / h), the leading edge and windward surface of the blades are subjected to continuous impact from high-speed two-phase flows carrying solid and liquid particles such as raindrops, ice crystals, dust, and salt spray. This "high-speed particle erosion" has become one of the most significant forms of damage leading to the failure of the blade's protective coating and consequently damaging the blade itself.

[0003] Most commercially available wind turbine blade coatings are based on traditional polyurethane or epoxy systems. However, erosion resistance requires coatings to possess both high hardness and high toughness. While polyurethane coatings can buffer impacts, their low hardness and modulus result in extremely high wear rates under the continuous "micro-cutting" action of sharp sand particles. Epoxy coatings, while wear-resistant, are brittle and prone to radial microcracks around the impact point under high-speed particle impact. These microcracks rapidly expand and interconnect under subsequent stress, leading to macroscopic fragmentation and flaking of the coating. Therefore, it is difficult to achieve a perfect balance of high hardness and high toughness in the same homogeneous coating. Consequently, stress waves generated by high-speed impacts are reflected and superimposed at the interface, easily inducing and accelerating the initiation and propagation of interfacial microcracks. Ultimately, this leads to large-area peeling of the coating from the edges or damage center, resulting in loss of protective function. After the coating wears down, the blade substrate is directly exposed, which not only alters the blade's precise aerodynamic shape and reduces power generation efficiency but also accelerates damage to the substrate itself, causing serious problems such as moisture intrusion and reduced structural strength, significantly increasing maintenance costs and safety hazards.

[0004] Currently, there is an urgent need to propose a solution to address the aforementioned technical problems. Summary of the Invention

[0005] In order to enable the coating structure formed by the coating to resist the cutting and abrasion of high-speed particles, and to efficiently absorb and disperse the impact kinetic energy, thereby achieving the optimal balance between hardness and toughness and significantly extending the service life of wind turbine blades under high-speed particle erosion, this application provides a coating for wind turbine blades and its preparation method.

[0006] In a first aspect, this application provides a coating for wind turbine blades, employing the following technical solution: A coating for wind turbine blades, comprising component A and component B, which are stored separately and mixed by weight in a ratio of (4-5):1 when used; Component A comprises the following raw materials in parts by weight: 40-60 parts of hydroxyl acrylic resin; 0.5-2 parts of ultraviolet absorber; Light stabilizer 0.5-2 parts; 1-1.5 parts of dispersant; Leveling agent 0.2-0.6 parts; Defoamer 0.1-0.3 parts; Solvent 10-25 parts; 8-15 parts of nano-toughening filler; 12-20 parts of dispersed wear-resistant filler; The nano-toughening filler is a core-shell structured rubber particle, with the core being butadiene-butyl acrylate copolymer and the shell being polymethyl methacrylate; The dispersed wear-resistant filler is glass flakes or ceramic flakes that have been surface-treated with a silane coupling agent; Component B is a curing agent.

[0007] By adopting the above technical solutions, acrylic resin itself possesses excellent weather resistance, gloss and color retention, and moderate hardness. The network structure formed by its reaction with the curing agent serves as an excellent mixing matrix, facilitating the finding of the optimal balance between hardness and toughness. UV absorbers and light stabilizers combat long-term outdoor UV aging, preventing resin backbone degradation that leads to coating chalking and embrittlement, thus ensuring long-term weather resistance. Dispersants, leveling agents, and defoamers guarantee the storage stability, workability, and final dense, defect-free coating of the multiphase, multi-filler system.

[0008] For the use of nano-toughening fillers, butadiene-butyl acrylate copolymer, a highly elastic rubber phase, is an efficient energy absorber. When the coating is impacted, these soft particles can absorb and dissipate a large amount of impact energy through their own large deformation, effectively preventing the initiation and propagation of microcracks. Polymethyl methacrylate has excellent compatibility with the acrylic resin matrix, which ensures that the rubber particles can be uniformly and stably dispersed in the resin, preventing agglomeration and achieving a strong interfacial bond with the matrix. The strong interface is the key to the effective transfer of stress from the brittle matrix to the flexible particles, thereby achieving toughening without losing too much hardness.

[0009] For the use of dispersed wear-resistant fillers, glass or ceramic flakes are plate-shaped hard fillers. They are arranged parallel to the substrate surface in the coating, forming a layered "brick and tile structure" that greatly resists the cutting and abrasion of high-speed particles. The use of silane coupling agents creates "molecular bridges" between inorganic flakes and organic resins, forming chemical bonds. This greatly enhances the interfacial bonding force, prevents the flakes from becoming stress concentration points and detachment points, and ensures that the hard phase can play its full role without introducing a fragile interface.

[0010] Meanwhile, when nano-toughened fillers and dispersed wear-resistant fillers are used together, they can play an excellent synergistic role. Not only do they utilize rubber particles to absorb energy and scales to disperse stress, so that impact energy is consumed in multiple stages rather than being conducted in a single stage, but they also cause cracks to deflect and diffract when they encounter scales and become passivated and branched when they encounter rubber particles. This forms a microstructure that combines rigidity and flexibility inside the coating. In this way, it can resist the cutting and abrasion of high-speed particles and efficiently absorb and disperse impact kinetic energy, achieving the optimal balance between hardness and toughness, and thus significantly extending the service life of wind turbine blades under high-speed particle erosion.

[0011] Preferably, the particle size of the nano-toughening filler is 120-200 nm, wherein the ratio of the core diameter to the shell thickness is (3-5):1.

[0012] By adopting the above technical solution, a particle size range of 120-200nm ensures sufficient volume for plastic deformation, preventing the stress waves from "bypassing" the particle size and hindering effective energy absorption, while also preventing excessive stress concentration due to excessively large particle size, which could become a crack initiation point. A core diameter to shell thickness ratio of (3-5):1 ensures efficient transfer of impact stress to the core, allowing the core to undergo large deformation and absorb energy. Simultaneously, the shell forms a strong bond with the acrylic resin matrix, exhibiting stable and excellent interfacial compatibility and stress transfer performance. Thus, the nano-toughening filler can exert a stable and optimal effect.

[0013] Preferably, the thickness of the dispersed wear-resistant filler is 1-5 μm, and its aspect ratio is 55-65.

[0014] By adopting the above technical solution, a layer thickness greater than 1 μm ensures sufficient bending stiffness of the dispersed wear-resistant filler, preventing brittle fracture or excessive bending under high-speed particle impact, thus effectively resisting the cutting and abrasion of high-speed particles. A layer thickness less than 5 μm prevents excessive thickness from increasing the brittleness of the dispersed wear-resistant filler and generating excessive internal stress during coating curing and shrinkage, which could lead to microcracks. An aspect ratio of 55-65 gives the dispersed wear-resistant filler excellent planar stress dispersion capability, rapidly converting the kinetic energy of high-speed particles into vibrational energy of the flake plane and dissipating it, preventing stress penetration of the coating. In this way, the dispersed wear-resistant filler can exert a stable and optimal corresponding effect.

[0015] Preferably, component A further contains 2-5 parts by weight of a functional additive, which is composed of silica-supported catalyst nanoparticles and microcapsule particles, with a weight ratio of silica-supported catalyst nanoparticles to microcapsule particles of 1:(5-10). The silica-supported catalyst nanoparticles were prepared by the following steps: The catalyst was dispersed in a mixed solvent of anhydrous ethanol and toluene, and then tetraethyl orthosilicate was added under nitrogen protection and ice-water bath conditions. After stirring and mixing, ammonia was added for catalytic hydrolysis. After reacting at 5-10℃ for 12-24h, the catalyst nanoparticles were obtained after centrifugation, washing and drying. In the silica-supported catalyst nanoparticles, the weight ratio of silica to catalyst is (4-6):1; The microcapsule particles were prepared by the following steps: S1. Preparation of prepolymer solution and emulsion: After mixing urea and formaldehyde solution, adjust the pH to 8.0-8.5 with triethanolamine, and stir the reaction at 70-75℃ for 55-65 min to obtain prepolymer solution; simultaneously, mix deionized water and emulsifier, add dicyclopentadiene, and emulsify at high speed of 8000-12000 rpm for 10-15 min to obtain emulsion; S2. Polymerization reaction: Take the emulsion obtained in step S1 and add it to the reaction vessel, then add the prepolymer solution obtained in step S1, adjust the pH to 3.5-4.0, stir and polymerize at 45-50℃ for 2-3 hours, and finally obtain microcapsule particles after neutralization, separation, washing and drying. The core-to-wall mass ratio of the microcapsule particles is (1-1.5):1.

[0016] By employing the above-mentioned technical solution, in the preparation of silica-supported catalyst nanoparticles, a dense amorphous silica shell is generated, completely encapsulating the catalyst's active sites. The catalyst is only released and activated when the silica shell breaks under stress. In the preparation of microcapsule particles, a wall material with high hardness, high brittleness, and high impact sensitivity can be formed. It is extremely prone to brittle fracture under high-speed particle impact. When the impact causes the microcapsule to rupture and release dicyclopentadiene, it triggers ring-opening metathesis polymerization upon contact with the catalyst, enabling chemical self-healing of the cracks. When silica-supported catalyst nanoparticles and microcapsule particles are used as functional additives, firstly, both are rigid particles, and their dispersion in the coating can improve the modulus and hardness of the coating, assisting the nano-toughening filler and the dispersed wear-resistant filler to play a better synergistic role; secondly, high-speed impact causes the microcapsules to rupture and release dicyclopentadiene, and at the same time, it shatters the silica shell of the adjacent silica-supported catalyst nanoparticles to release the catalyst. The two polymerize instantly upon contact, filling and healing cracks in situ, which can effectively inhibit the irreversible propagation of microcracks under stress and prevent them from expanding into macro-cracks; at the same time, the polymer formed above is doped with the ruptured silica shell and microcapsule particle wall material, which can build a coordinated connection network between the nano-toughening filler and the dispersed wear-resistant filler, enhance the synergistic effect between the nano-toughening filler and the dispersed wear-resistant filler, and form a better multi-dimensional synergistic mechanism, thereby bringing excellent performance improvement in resisting the cutting and shearing of high-speed particles and in efficiently absorbing and dispersing impact kinetic energy.

[0017] Meanwhile, the weight ratio of silica to catalyst is (4-6):1, which ensures both storage stability and mechanical trigger sensitivity; the core-to-wall mass ratio of microcapsule particles is (1-1.5):1, which not only ensures that the microcapsule particles can fill and repair microcracks after rupture, but also protects the core material from cracking during construction and slight friction, and can break rapidly under the stress of high-speed particle impact; finally, the weight ratio of silica-supported catalyst nanoparticles to microcapsule particles is 1:(5-10), which avoids the decrease in stability due to excessive catalyst or the incomplete repair due to insufficient catalyst, thus ensuring that the functional additives exert excellent and stable corresponding effects.

[0018] Preferably, the silica-supported catalyst nanoparticles have a particle size of 30-60 nm; the microcapsule particles have a particle size of 90-150 nm.

[0019] By adopting the above technical solution, the size matching of the silica-supported catalyst nanoparticles and microcapsule particles ensures their high response sensitivity and stable repair of microcracks at the microscale, thereby making the coating exhibit better instantaneous response capability and microstructure stability under high-speed impact.

[0020] Preferably, component A further comprises 4-6 parts by weight of a composite functional filler, which is prepared from sodium acetate trihydrate and molybdenum disulfide by the following method: Sodium acetate trihydrate was dispersed in anhydrous ethanol, and molybdenum disulfide was added for ultrasonic and high-speed shearing treatment. Finally, after rotary evaporation and cooling grinding, the composite functional filler was obtained by sieving. The weight ratio of sodium acetate trihydrate to molybdenum disulfide is (6-7):1.

[0021] By adopting the above technical solution, in the preparation of composite functional fillers, molybdenum disulfide nanosheets are re-stacked and compacted on the surface of sodium acetate trihydrate to form a dense nano-barrier layer. When the composite functional filler is applied to the coating for wind turbine blades, when the coating is impacted by high-speed particles, the generated heat energy causes sodium acetate trihydrate to absorb heat and undergo a solid-liquid transformation, thereby reducing the generation of thermal stress. Meanwhile, molybdenum disulfide can provide sufficient hardness and lubricity, thus significantly reducing the erosion wear rate. Through the special combination of sodium acetate trihydrate and molybdenum disulfide, a thermal management system is constructed in the coating. The synergistic compounding between the two further improves the application stability of the coating structure under high-speed particle impact, thereby significantly extending the service life of wind turbine blades under high-speed particle erosion.

[0022] Preferably, the weight ratio of sodium acetate trihydrate to molybdenum disulfide is 6.5:1.

[0023] By adopting the above technical solution, it is ensured that molybdenum disulfide can stably provide instantaneous lubrication, reducing the cutting force of particles on the coating; and when dealing with high-speed erosion, the impact kinetic energy is converted into heat energy, and sodium acetate trihydrate rapidly absorbs heat and undergoes a phase change; thus ensuring that the composite functional filler plays a stable and better role in the application process.

[0024] Preferably, the hydroxyl content of the hydroxyl acrylic resin is 2.5-4.0%, and the glass transition temperature is 40-60°C.

[0025] By adopting the above technical solution, both the skeleton hardness to resist continuous wear and the toughness margin to cope with instantaneous impact are provided, which is a stable matrix foundation to support the synergistic effect of the entire complex packing system.

[0026] Preferably, the solvent is a mixture of propylene glycol methyl ether acetate, butyl acetate and xylene, and the weight ratio of propylene glycol methyl ether acetate, butyl acetate and xylene is (1-1.6): (0.8-1.4):1.

[0027] By adopting the above technical solution, a "fast-medium-slow" synergistic evaporation gradient was established for the solvent, which precisely controlled the curing kinetics of the coating, thereby ensuring that each component raw material could exert an excellent and stable synergistic effect.

[0028] Secondly, this application provides a method for preparing a coating for wind turbine blades, employing the following technical solution: A method for preparing a coating for wind turbine blades includes the following steps: (1) Prepare raw materials containing hydroxyl acrylic resin, ultraviolet absorber, light stabilizer, dispersant, leveling agent, defoamer, solvent, nano toughening filler and dispersing wear-resistant filler according to the formula ratio; (2) Take the hydroxyl acrylic resin, dispersant, defoamer and solvent from step (1) and mix them. Then add the nano toughening filler and the dispersed wear-resistant filler and mix them. Finally add the ultraviolet absorber, light stabilizer and leveling agent and mix them evenly to obtain component A; component B is the curing agent. (3) After mixing components A and B in step (2) according to the usage ratio, the coating for wind turbine blades is obtained.

[0029] In summary, this application has the following beneficial effects: 1. When nano-toughening filler and dispersing wear-resistant filler are used in combination in this application, the synergistic compounding between the two not only utilizes rubber particles to absorb energy and scales to disperse stress, so that impact energy is consumed in multiple stages rather than being conducted in a single stage, but also causes cracks to be deflected and diffracted when they encounter scales, and to be passivated and branched when they encounter rubber particles, thereby forming a microstructure that combines rigidity and flexibility inside the coating. In this way, it can resist the cutting and cutting of high-speed particles, and efficiently absorb and disperse impact kinetic energy, achieving the optimal balance between hardness and toughness, thereby significantly extending the service life of wind turbine blades under high-speed particle erosion. 2. By adding functional additives composed of silica-supported catalyst nanoparticles and microcapsule particles, this application can effectively suppress the irreversible propagation of microcracks under stress when the coating structure is eroded by high-speed particles, prevent them from expanding into macrocracks, and enhance the synergistic effect between nano-toughening fillers and dispersing wear-resistant fillers, thereby bringing excellent performance improvement in resisting the cutting and cutting of high-speed particles and efficiently absorbing and dispersing impact kinetic energy. 3. This application constructs a thermal management system in the coating by adding a composite functional filler specially prepared from sodium acetate trihydrate and molybdenum disulfide, which further improves the application stability of the coating structure under high-speed particle impact, thereby significantly extending the service life of wind turbine blades under high-speed particle erosion. Detailed Implementation

[0030] The present application will be further described in detail below with reference to preparation examples, embodiments and comparative examples.

[0031] Unless otherwise specified, all raw materials used in the preparation examples, embodiments and comparative examples of this application are commercially available.

[0032] The ultraviolet absorber was purchased from UV-234. The light stabilizer was purchased from hindered amine light stabilizer HS-508 (292); The dispersant was purchased from TEGO 655 wetting and dispersing agent. The leveling agent was purchased from BYK333. The defoamer was purchased from Tego Foamex 810 paint defoamer from Winwin Technology. The curing agent is isophorone diamine curing agent; The glass flakes have a silica content of 70%, a porosity of 1.5%, and a Barcol hardness of 57.

[0033] Preparation examples of raw materials and / or intermediates Preparation Example 1 A silica-supported catalyst nanoparticle was prepared by the following steps: The catalyst was dispersed in a mixed solvent of anhydrous ethanol and toluene at a ratio of 1g:300mL. Then, tetraethyl orthosilicate was added under nitrogen protection and an ice-water bath. After stirring and mixing, 28wt% ammonia water (5% of the total volume of the mixed solvent) was added for catalytic hydrolysis. The reaction was carried out at 5-10℃ for 12-24h (20h at 5℃ in this preparation example). After centrifugation, washing with anhydrous ethanol and vacuum drying, silica-supported catalyst nanoparticles were obtained.

[0034] Note: In the above operation, the catalyst is a second-generation Grubbs catalyst, and the volume ratio of anhydrous ethanol to toluene in the mixed solvent is 2:1; the weight ratio of silica to catalyst in the silica-supported catalyst nanoparticles is 5:1; the particle size of the silica-supported catalyst nanoparticles is 45 nm.

[0035] Preparation Example 2 A silica-supported catalyst nanoparticle differs from Preparation Example 1 in that the weight ratio of silica to catalyst is 4:1.

[0036] Preparation Example 3 A silica-supported catalyst nanoparticle differs from Preparation Example 1 in that the weight ratio of silica to catalyst is 6:1.

[0037] Preparation Example 4 A silica-supported catalyst nanoparticle, which differs from Preparation Example 1 in that the silica-supported catalyst nanoparticle has a particle size of 30 nm.

[0038] Preparation Example 5 A silica-supported catalyst nanoparticle, which differs from Preparation Example 1 in that the silica-supported catalyst nanoparticle has a particle size of 60 nm.

[0039] Preparation Example 6 A microcapsule particle is prepared by the following steps: S1. Preparation of prepolymer solution and emulsion: Urea and 37wt% formaldehyde solution were mixed at a weight ratio of 1:1.5, and the pH was adjusted to 8.0-8.5 with triethanolamine (pH 8.2 in this preparation example). The mixture was stirred at 70-75℃ for 55-65 min (stirred at 72℃ for 60 min in this preparation example) to obtain the prepolymer solution. Simultaneously, deionized water and emulsifier were mixed, and dicyclopentadiene was added. The mixture was emulsified at 8000-12000 rpm for 10-15 min (10000 rpm for 12 min in this preparation example) to obtain the emulsion. S2. Polymerization reaction: The emulsion obtained in step S1 is added to the reaction vessel, followed by the prepolymer solution obtained in step S1. The pH is adjusted to 3.5-4.0 (pH is 3.5 in this preparation example), and polymerization is carried out by stirring at 45-50℃ for 2-3 hours (pH is 47.5℃ for 2.5 hours in this preparation example). Finally, after neutralization, separation, washing and drying, microcapsule particles are obtained.

[0040] Note: In the above operation, the emulsifier is sodium dodecyl sulfate, which accounts for 0.6 wt% of deionized water; the core-to-wall mass ratio of the microcapsule particles is 1.25:1; and the particle size of the microcapsule particles is 120 nm.

[0041] Preparation Example 7 One type of microcapsule particle differs from Preparation Example 6 in that the core-to-wall mass ratio of the microcapsule particle is 1:1.

[0042] Preparation Example 8 One type of microcapsule particle differs from Preparation Example 6 in that the core-to-wall mass ratio of the microcapsule particle is 1.5:1.

[0043] Preparation Example 9 One type of microcapsule particle differs from Preparation Example 6 in that the microcapsule particle has a particle size of 90 nm.

[0044] Preparation Example 10 One type of microcapsule particle differs from Preparation Example 6 in that the microcapsule particle has a particle size of 150 nm.

[0045] Preparation Example 11 A composite functional filler is prepared from sodium acetate trihydrate and molybdenum disulfide by the following method: Sodium acetate trihydrate was dispersed in anhydrous ethanol at a ratio of 1g:100mL, and then molybdenum disulfide was added. The mixture was subjected to ultrasonic treatment and high-speed shearing at 5000rpm for 1 hour. Finally, after rotary evaporation and cooling grinding, the composite functional filler was obtained by passing it through a 400-mesh sieve.

[0046] Note: In the above operation, the average particle size of sodium acetate trihydrate is 10 μm, the average flake size of molybdenum disulfide is 2 μm, and the weight ratio of sodium acetate trihydrate to molybdenum disulfide is 6.5:1.

[0047] Preparation Example 12 A composite functional filler differs from Preparation Example 11 in that the weight ratio of sodium acetate trihydrate to molybdenum disulfide is 6:1.

[0048] Preparation Example 13 A composite functional filler differs from Preparation Example 11 in that the weight ratio of sodium acetate trihydrate to molybdenum disulfide is 7:1.

[0049] Example Example 1

[0050] A coating for wind turbine blades comprises component A and component B, which are stored separately and mixed in a weight ratio of 4.5:1 when used, and is prepared by the following steps: (1) Prepare raw materials containing hydroxyl acrylic resin, ultraviolet absorber, light stabilizer, dispersant, leveling agent, defoamer, solvent, nano toughening filler and dispersing wear-resistant filler according to the formula ratio; (2) Take the hydroxyl acrylic resin, dispersant, defoamer and solvent from step (1) and mix them. Then add the nano toughening filler and the dispersed wear-resistant filler and mix them. Finally add the ultraviolet absorber, light stabilizer and leveling agent and mix them evenly to obtain component A; component B is the curing agent. (3) After mixing components A and B in step (2) according to the usage ratio, the coating for wind turbine blades is obtained.

[0051] Note: In the above operation, the raw materials and corresponding weight parts of component A are shown in Table 1. The nano-toughening filler is a core-shell structured rubber particle, with the core being butadiene-butyl acrylate copolymer and the shell being polymethyl methacrylate, with a particle size of 160 nm, wherein the ratio of core diameter to shell thickness is 4:1. The preparation of the nano-toughened filler is as follows: 90 g of deionized water, 1.0 g of SDS, and 0.5 g of OP-10 were added to a container and stirred to dissolve. Then, 15 g of butyl acrylate, 2 g of methacrylic acid, and 0.2 g of divinylbenzene were added for shear emulsification to obtain a pre-emulsion. Then, 100 g of deionized water and 0.5 g of SDS were added to a high-pressure reactor. After purging with nitrogen to remove oxygen, 0.2 g of potassium persulfate was added. The temperature was raised to 70 °C and 10 g of butadiene was added. The pre-emulsion was then added dropwise at a rate of 1 mL / min. Finally, the reaction was maintained at 75 °C for 3 h to obtain a core-seed emulsion. The core-seed emulsion was heated to 80 °C and MMA was added dropwise at a very slow rate of 0.5 mL / min. After the addition was completed, the reaction was continued at 80 °C for 2 h. The temperature was then raised to 85 °C and maintained for 1 h. After cooling to 40 °C, 5 wt% calcium chloride solution was added to break the emulsion. The mixture was filtered to obtain a white flocculent precipitate, which was washed and dried to obtain the final product.

[0052] The dispersed wear-resistant filler is glass flakes surface-treated with a silane coupling agent, with a flake thickness of 3 μm and an aspect ratio of 60. The preparation of the silane coupling agent surface-treated glass flakes is as follows: KH-560 silane coupling agent is added to a mixed solvent of ethanol / water (9:1) at a ratio of 1 g:0.15 L to obtain a treatment solution; then, glass flakes are ultrasonically dispersed in the treatment solution at a ratio of 1 kg:1.5 L, stirred and reacted at 65 °C for 5 h, and finally obtained after centrifugation, washing and drying.

[0053] The hydroxyl content of the hydroxyl acrylic resin is 2.25%, and the glass transition temperature is 50℃.

[0054] The solvent is a mixture of propylene glycol methyl ether acetate, butyl acetate and xylene, and the weight ratio of propylene glycol methyl ether acetate, butyl acetate and xylene is 1.4:1.1:1. Example 2-3

[0055] A coating for wind turbine blades differs from Example 1 in that the raw materials and corresponding weight parts of component A are shown in Table 1.

[0056] Table 1. Composition of Component A in Examples 1-3 and corresponding weight parts (parts / kg) Example 4

[0057] A coating for wind turbine blades differs from Example 1 in that the weight ratio of component A to component B is 4:1. Example 5

[0058] A coating for wind turbine blades differs from Example 1 in that the weight ratio of component A to component B is 5:1. Example 6

[0059] A coating for wind turbine blades differs from Example 1 in that the nano-toughening filler is a core-shell structured rubber particle with a core of butadiene-butyl acrylate copolymer and a shell of polymethyl methacrylate, and a particle size of 120 nm, wherein the ratio of core diameter to shell thickness is 3:1. Example 7

[0060] A coating for wind turbine blades differs from Example 1 in that the nano-toughening filler is a core-shell structured rubber particle with a core of butadiene-butyl acrylate copolymer and a shell of polymethyl methacrylate, and a particle size of 200 nm, wherein the ratio of core diameter to shell thickness is 5:1. Example 8

[0061] A coating for wind turbine blades differs from Example 1 in that the dispersed abrasion-resistant filler is glass flakes surface-treated with a silane coupling agent, with a flake thickness of 1 μm and an aspect ratio of 55. Example 9

[0062] A coating for wind turbine blades differs from Example 1 in that the dispersed abrasion-resistant filler is glass flakes surface-treated with a silane coupling agent, with a flake thickness of 5 μm and an aspect ratio of 65. Example 10

[0063] A coating for wind turbine blades differs from Example 1 in that the hydroxyl content of the hydroxyl acrylic resin is 2.5% and the glass transition temperature is 40°C. Example 11

[0064] A coating for wind turbine blades differs from Example 1 in that the hydroxyl content of the hydroxyl acrylic resin is 4.0% and the glass transition temperature is 60°C. Example 12

[0065] A coating for wind turbine blades differs from Example 1 in that the solvent is a mixture of propylene glycol methyl ether acetate, butyl acetate, and xylene, and the weight ratio of propylene glycol methyl ether acetate, butyl acetate, and xylene is 1:0.8:1. Example 13

[0066] A coating for wind turbine blades differs from Example 1 in that the solvent is a mixture of propylene glycol methyl ether acetate, butyl acetate, and xylene, and the weight ratio of propylene glycol methyl ether acetate, butyl acetate, and xylene is 1.6:1.4:1. Example 14

[0067] A coating for wind turbine blades differs from Example 1 in that component A also contains 3.5 parts by weight of a functional additive. The functional additive consists of silica-supported catalyst nanoparticles and microcapsule particles, with a weight ratio of silica-supported catalyst nanoparticles to microcapsule particles of 1:7.5. It is added simultaneously with nano-toughening fillers and dispersed wear-resistant fillers. The silica-supported catalyst nanoparticles were obtained in Preparation Example 1, and the microcapsule particles were obtained in Preparation Example 6. Example 15

[0068] A coating for wind turbine blades differs from Example 14 in that the functional additives are added in 2 parts by weight. Example 16

[0069] A coating for wind turbine blades differs from Example 14 in that the functional additives are added in 5 parts by weight. Example 17

[0070] A coating for wind turbine blades differs from that in Example 14 in that the weight ratio of silica-supported catalyst nanoparticles to microcapsule particles is 1:5. Example 18

[0071] A coating for wind turbine blades differs from that of Example 14 in that the weight ratio of silica-supported catalyst nanoparticles to microcapsule particles is 1:10. Example 19

[0072] A coating for wind turbine blades, which differs from Example 14 in that the silica-supported catalyst nanoparticles are obtained from Preparation Example 2. Example 20

[0073] A coating for wind turbine blades, which differs from Example 14 in that the silica-supported catalyst nanoparticles are obtained from Preparation Example 3. Example 21

[0074] A coating for wind turbine blades, which differs from Example 14 in that the silica-supported catalyst nanoparticles are obtained from Preparation Example 4. Example 22

[0075] A coating for wind turbine blades, which differs from Example 14 in that the silica-supported catalyst nanoparticles are obtained from Preparation Example 5. Example 23

[0076] A coating for wind turbine blades, which differs from Example 14 in that the microcapsule particles are obtained from Preparation Example 7. Example 24

[0077] A coating for wind turbine blades, which differs from Example 14 in that the microcapsule particles are obtained from Preparation Example 8. Example 25

[0078] A coating for wind turbine blades, which differs from Example 14 in that the microcapsule particles are obtained from Preparation Example 9. Example 26

[0079] A coating for wind turbine blades, which differs from Example 14 in that the microcapsule particles are obtained from Preparation Example 10. Example 27

[0080] A coating for wind turbine blades differs from Example 1 in that component A contains 5 parts by weight of a composite functional filler obtained from Preparation Example 11, and the composite functional filler, nano-toughening filler, and dispersed wear-resistant filler are added and used simultaneously. Example 28

[0081] A coating for wind turbine blades differs from Example 27 in that the composite functional filler is added in 4 parts by weight. Example 29

[0082] A coating for wind turbine blades differs from Example 27 in that the composite functional filler is added in 6 parts by weight. Example 30

[0083] A coating for wind turbine blades, which differs from Example 27 in that the composite functional filler is obtained from Preparation Example 12. Example 31

[0084] A coating for wind turbine blades, which differs from Example 27 in that the composite functional filler is obtained from Preparation Example 13.

[0085] Comparative Example Comparative Example 1 A coating for wind turbine blades differs from Example 1 in that no nano-toughening filler is used in component A.

[0086] Comparative Example 2 A coating for wind turbine blades, which differs from Example 1 in that no dispersed abrasion-resistant filler is used in component A.

[0087] Comparative Example 3 A coating for wind turbine blades differs from Example 1 in that component A does not use nano-toughening fillers and dispersed abrasion-resistant fillers.

[0088] Comparative Example 4 A coating for wind turbine blades, which differs from Example 14 in that component A does not use nano-toughening fillers and dispersed abrasion-resistant fillers.

[0089] Comparative Example 5 A coating for wind turbine blades, which differs from Example 27 in that component A does not use nano-toughening fillers and dispersed abrasion-resistant fillers.

[0090] Performance testing Test samples: The wind turbine blade coatings obtained in Examples 1-31 were selected as test samples 1-31, and the wind turbine blade coatings obtained in Comparative Examples 1-5 were selected as control samples 1-5.

[0091] Experimental method: Glass fiber reinforced polymer (GFRP) was used as the substrate, and a coating for wind turbine blades was sprayed onto it. The coating was cured at 25℃ and 55%RH for 7 days to obtain a coating structure with a dry film thickness of 100μm. According to the requirements of the testing standard GB / T 20624.2, the above-mentioned coating structure was subjected to a drop hammer impact test using a drop hammer impact testing machine. The mass of the drop hammer was 1kg and the diameter of the punch was 12.7mm. The maximum impact energy that just prevented the coating structure from cracking was obtained and recorded as the initial value A1. Then, the coating structure obtained from the same type of wind turbine blade coating was used. First, a high-speed rain erosion test was conducted according to the requirements of the test standard ISO / TS 19392-2. The sample with the coating structure was fixed at the end of the rotating arm, ensuring that the leading edge of the windward side was facing the direction of rotation. The water droplet diameter was controlled at 2 mm, the velocity at 90 m / s, and the impact angle at 90° for 4 hours. Next, a solid particle erosion test was conducted according to the test standard ASTM D968, using 100-mesh quartz sand as the abrasive. The spray gun pressure was set at 0.5 MPa, the incident angle at 90°, and the spray distance at 100 mm for 1 hour. Finally, the same drop hammer impact test was conducted to obtain the maximum impact energy that just prevented the coating structure from cracking, which was recorded as the erosion value A2. The value calculated as “A2 / A1×100%” is recorded as the coating structure strength retention rate. The higher the coating structure strength retention rate, the better the coating structure’s ability to resist the cutting and abrasion of high-speed particles and to efficiently absorb and disperse impact kinetic energy, and the better the overall stability during application.

[0092] After performing the above tests on test samples 1-31 and control samples 1-5, the test results are recorded in Table 2.

[0093] Table 2 Test results of test samples 1-31 and control samples 1-5 As can be seen from Examples 1-13 and Comparative Examples 1-3, and Table 2, when the present application uses nano-toughening filler and dispersed wear-resistant filler in combination, the synergistic effect of their compounding significantly improves the coating structure strength retention rate during the above tests. This indicates that both filler and dispersed filler can resist the penetration and cutting of high-speed particles in the coating structure, while also efficiently absorbing and dispersing impact kinetic energy, achieving an optimal balance between hardness and toughness, thereby significantly extending the service life of wind turbine blades under high-speed particle erosion. Furthermore, while adding either nano-toughening filler or dispersed wear-resistant filler individually can bring about a corresponding improvement effect, the improvement is limited, and the sum of the improvement effects of using either filler alone is far less than the superior effect of their compounding. Therefore, the combination of nano-toughening filler and dispersed wear-resistant filler can bring about a significant improvement effect of 1+1>2.

[0094] As can be seen from Examples 1 and 14-26, and Table 2, the addition of functional additives composed of silica-supported catalyst nanoparticles and microcapsule particles significantly improves the coating structure's resistance to high-speed particle penetration and cutting, as well as its efficient absorption and dispersion of impact kinetic energy when subjected to high-speed particle erosion. This results in a significant improvement in the strength retention rate of the tested coating structure. Furthermore, comparing Comparative Examples 3-4 with Table 2, it is evident that the improvement effect brought about by the application of functional additives is significantly diminished without the use of nano-toughening fillers and dispersing wear-resistant fillers. Therefore, in addition to their own excellent effects, functional additives also promote the compounding effect of nano-toughening fillers and dispersing wear-resistant fillers.

[0095] As can be seen from Examples 1 and 27-31 and Table 2, this application, by adding a composite functional filler specially prepared from sodium acetate trihydrate and molybdenum disulfide, further improves the stability of the coating structure under high-speed particle impact, thereby significantly extending the service life of wind turbine blades under high-speed particle erosion. Furthermore, comparing Comparative Examples 3 and 5 and Table 2, it can be seen that without the use of nano-toughening fillers and dispersed wear-resistant fillers, the corresponding improvement effect brought about by the application of composite functional fillers will be significantly reduced. This demonstrates that, in addition to its own excellent performance, the composite functional filler also exhibits excellent synergistic effects with nano-toughening fillers and dispersed wear-resistant fillers.

[0096] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A coating for wind turbine blades, characterized in that, Includes components A and B, which are stored separately and mixed by weight in a ratio of (4-5):1 when used; Component A comprises the following raw materials in parts by weight: 40-60 parts of hydroxyl acrylic resin; 0.5-2 parts of ultraviolet absorber; Light stabilizer 0.5-2 parts; 1-1.5 parts of dispersant; Leveling agent 0.2-0.6 parts; Defoamer 0.1-0.3 parts; Solvent 10-25 parts; 8-15 parts of nano-toughening filler; 12-20 parts of dispersed wear-resistant filler; The nano-toughening filler is a core-shell structured rubber particle, with the core being butadiene-butyl acrylate copolymer and the shell being polymethyl methacrylate; The dispersed wear-resistant filler is glass flakes or ceramic flakes that have been surface-treated with a silane coupling agent; Component B is a curing agent.

2. The coating for wind turbine blades according to claim 1, characterized in that: The nano-toughening filler has a particle size of 120-200 nm, wherein the ratio of core diameter to shell thickness is (3-5):

1.

3. The coating for wind turbine blades according to claim 1, characterized in that: The thickness of the dispersed wear-resistant filler is 1-5 μm, and its aspect ratio is 55-65.

4. The coating for wind turbine blades according to claim 1, characterized in that: The A component also contains 2-5 parts by weight of functional additives, which are composed of silica-supported catalyst nanoparticles and microcapsule particles, with a weight ratio of silica-supported catalyst nanoparticles to microcapsule particles of 1:(5-10). The silica-supported catalyst nanoparticles were prepared by the following steps: The catalyst was dispersed in a mixed solvent of anhydrous ethanol and toluene, and then tetraethyl orthosilicate was added under nitrogen protection and ice-water bath conditions. After stirring and mixing, ammonia was added for catalytic hydrolysis. After reacting at 5-10℃ for 12-24h, the catalyst nanoparticles were obtained after centrifugation, washing and drying. In the silica-supported catalyst nanoparticles, the weight ratio of silica to catalyst is (4-6):1; The microcapsule particles were prepared by the following steps: S1. Preparation of prepolymer solution and emulsion: After mixing urea and formaldehyde solution, adjust the pH to 8.0-8.5 with triethanolamine, and stir the reaction at 70-75℃ for 55-65 min to obtain prepolymer solution; simultaneously, mix deionized water and emulsifier, add dicyclopentadiene, and emulsify at high speed of 8000-12000 rpm for 10-15 min to obtain emulsion; S2. Polymerization reaction: Take the emulsion obtained in step S1 and add it to the reaction vessel, then add the prepolymer solution obtained in step S1, adjust the pH to 3.5-4.0, stir and polymerize at 45-50℃ for 2-3 hours, and finally obtain microcapsule particles after neutralization, separation, washing and drying. The core-to-wall mass ratio of the microcapsule particles is (1-1.5):

1.

5. The coating for wind turbine blades according to claim 4, characterized in that: The silica-supported catalyst nanoparticles have a particle size of 30-60 nm; the microcapsule particles have a particle size of 90-150 nm.

6. The coating for wind turbine blades according to claim 1, characterized in that: The A component also contains 4-6 parts by weight of a composite functional filler, which is prepared from sodium acetate trihydrate and molybdenum disulfide by the following method: Sodium acetate trihydrate was dispersed in anhydrous ethanol, and molybdenum disulfide was added for ultrasonic and high-speed shearing treatment. Finally, after rotary evaporation and cooling grinding, the composite functional filler was obtained by sieving. The weight ratio of sodium acetate trihydrate to molybdenum disulfide is (6-7):

1.

7. The coating for wind turbine blades according to claim 6, characterized in that: The weight ratio of sodium acetate trihydrate to molybdenum disulfide is 6.5:

1.

8. The coating for wind turbine blades according to claim 1, characterized in that: The hydroxyl content of the hydroxyl acrylic resin is 2.5-4.0%, and the glass transition temperature is 40-60℃.

9. The coating for wind turbine blades according to claim 1, characterized in that: The solvent is a mixture of propylene glycol methyl ether acetate, butyl acetate and xylene, and the weight ratio of propylene glycol methyl ether acetate, butyl acetate and xylene is (1-1.6): (0.8-1.4):

1.

10. The coating for wind turbine blades according to claim 1, characterized in that: Includes the following steps: (1) Prepare raw materials containing hydroxyl acrylic resin, ultraviolet absorber, light stabilizer, dispersant, leveling agent, defoamer, solvent, nano toughening filler and dispersing wear-resistant filler according to the formula ratio; (2) Take the hydroxyl acrylic resin, dispersant, defoamer and solvent from step (1) and mix them. Then add the nano toughening filler and the dispersed wear-resistant filler and mix them. Finally add the ultraviolet absorber, light stabilizer and leveling agent and mix them evenly to obtain component A; component B is the curing agent. (3) After mixing components A and B in step (2) according to the usage ratio, the coating for wind turbine blades is obtained.